The Causes of Stress on Elderly During Pandemic of Covid-19: A Systematic Review - Yulianto, Sigit; Windarwati, Heni Dwi (Indonesian Journal of Global Health Research, 2024)
The problem of COVID-19 was able to infect all people regardless of age group, however the elderly of 60 years and above were the more vulnerable population to exposure to the corona virus. This research was aimed to identify the causes of stress on elderly during pandemic of COVID-19. Methods: A systematic search through three databases: ScienceDirect, PubMed, and ProQuest, by using these following terms “causes of psychological”, “stress”, “cause”, “elderly”, “older adult”, and “COVID-19”. The search was restricted on publication during December 2019 – October 2020. The article was selected by exerting PRISMA, the total of 16 articles were analyzed through systematic review. Findings: Based on the synthetic finding, this research found that the stress on elderly was divided into two factors. The internal factors were chronic disease, loneliness, emotional condition, and self-endurance, while external factor were lack of family support, regional lockdown, lack of communication with neighbor, reduced income, and lack of physical exercise. Conclusions: This research finding referred to risk factors from wither internal factor or external factor which could cause the stress on elderly during this pandemic of COVID-19.